Carbamazepine responsive typewriter tinnitus from basilar invagination. Issue 4 (1st April 2010) - Nam, Eui-Cheol; Handzel, Ophir; Levine, Robert A
Abstract : Basilar invagination due to a congenital skeletal disorder kinked the brainstem at the ponto-medullary junction causing both auditory nerves to make an acute turn at the porus acousticus. The associated bilateral asynchronous clicking tinnitus responded to carbamazepine.